Zulewski's clinical score and its validation in hypothyroid patients: Experience in a tertiary care center in Western India - Prachi Srivastava; Jaideep Khare; Sandeep Rai; Jaishree Ghanekar (Wolters Kluwer Medknow Publications, 2020)
Introduction: Hypothyroidism is a common endocrine disorder with the prevalence of approximately 10.95% among the general population in India. Aim: The aim of this study was to evaluate the prevalence of various signs and symptoms of hypothyroidism and to correlate with the biochemical investigations and clinical Zulewski's score in hypothyroid patients. Materials and Methods: A total of 207 patients of hypothyroidism attending our endocrine and medicine outpatient department were included in the study. Clinical data including signs and symptoms of hypothyroidism were obtained by interviewing the patients and referring to records. Prevalence of various signs and symptoms was recorded along with anthropometric indices, and Zulewski's score was calculated. Thyroid function tests were performed along with other laboratory investigations according to the patient condition. Results: Patients aged between 18 and 72 years were included in the study with male-to-female ratio was 51:156. Patients had different signs and symptoms of clinical hypothyroidism, and 74.4% of patients had ≥5 components of Zulewski's score. Most and least common defining criteria of Zulewski's score were dry skin and hearing impairment, respectively. Conclusion: Zulewski's clinical scoring is an economic and effective tool for identifying clinical hypothyroidism and can be used as clinical basis for starting levothyroxine replacement therapy if due to unavoidable reasons, it is difficult to get thyroid function test.